The impact of agriculture on the environment in Gorenjske Dobrave from the perspective of energy consumption - Urbanc, Mimi (Geografski zbornik, 1998)
Under the influence of natural and social conditions, intensive dairy cattle breeding developed in the last decade in part of Gorenjske Dobrave, an area northwest of Ljubljana in the foothills of the Kamniške-Savinjske Alps. This rigorous specialization has brought exceptional yields but at the same time aroused concern due to its possible negative impact on the environment. This study attemps to evaluate the agriculture from the viewpoint of its effect on the landscape and to point to the possibilities for environmental pollution using a variety of indicators: yield per hectare, the impact of cattle breeding on the land, land use, and energy intensity.
Keywords: agrarna geografija; agriculture; animal husbandry; Gorenjske Dobrave; kmetijstvo; onesnaževanje tal; onesnaževanje voda; pokrajinska ekologija; Slovenia; Slovenija; živinoreja